2021
DOI: 10.1002/ansa.202000144
|View full text |Cite
|
Sign up to set email alerts
|

A review of retention mechanism studies for packed column supercritical fluid chromatography

Abstract: The packed column supercritical fluid chromatography has risen as a promising alternative separation technique to the conventional liquid chromatography and gas chromatography. Although the packed column supercritical fluid chromatography has many advantages compared to other chromatographic techniques, its separation mechanism is not fully understood due to the complex combination effects of many chromatographic parameters on separation quality and the lacking of global strategies for studying separation mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 163 publications
(481 reference statements)
0
3
0
Order By: Relevance
“…Regarding the effect of water usage on chiral separation, the results demonstrated that a dramatic gain in the separation efficiency of hydrophilic phases-compared to hydrophobic phases-also leads to a decrease in the retention times of hydrophilic stationary phases [28]. Other applications of using water as an additive are reported in [33,34].…”
Section: Using Water As An Additive In Sfcmentioning
confidence: 99%
“…Regarding the effect of water usage on chiral separation, the results demonstrated that a dramatic gain in the separation efficiency of hydrophilic phases-compared to hydrophobic phases-also leads to a decrease in the retention times of hydrophilic stationary phases [28]. Other applications of using water as an additive are reported in [33,34].…”
Section: Using Water As An Additive In Sfcmentioning
confidence: 99%
“…Lesellier and West have applied the LSER model on a broad spectrum of stationary phases used in packed column SFC to describe the retention behavior and classify the columns [122][123][124][125][126][127]. The unified classification of stationary phases is displayed as a spider diagram (Figure 3), where the individual stationary phases are plotted and grouped based on the retention behavior and selectivity [26,[128][129][130]. This diagram can be easily used when searching for columns with similar or orthogonal selectivity during method development and for a quick insight into the retention behavior of stationary phase with the same chemistry but from different manufacturers.…”
Section: Packed Sfc Columns In Analytical-scalementioning
confidence: 99%
“…In recent years, ultrahigh-performance supercritical fluid chromatography (UHPSFC) has established a strong position among the separation techniques in various application fields. , The unique physicochemical properties of the mobile phase consisting of carbon dioxide, organic modifier, and additive, allow the separation of nonpolar, medium polar to polar compounds. , Due to the many possibilities of method tuning, including not only mobile phase composition and stationary phase selection but also pressure, temperature, and flow rate adjustment, the continuous change of conditions from SFC to LC is possible. In the early 1990s, the first attempts to separate medium polar compounds were made when using polar packed columns in SFC and/or unified chromatography (UC) as a concept where the single chromatographic system could carry out analysis in different modes, including all GC, LC, and SFC .…”
mentioning
confidence: 99%